Annual Movements of Acoustic-Tagged White Sturgeon in the Lower Reaches of the Fraser River and its Tributaries. Issue 4 (4th July 2017) - Robichaud, David; English, Karl K.; Nelson, Troy C.
Abstract: Details of the spatial ecology of White Sturgeon Acipenser transmontanus in the lower Fraser River, British Columbia, are needed for habitat conservation, assessments of impacts from spatially delimited threats, and refinement of abundance estimation methods. The abundance of threatened lower Fraser River White Sturgeon is assessed annually using a Bayesian, closed-population, mark–recapture model. If individuals make prolonged departures from the lower Fraser River, either into marine waters or a tributary, the validity of the model's assumed closed population is questionable. There is also concern that fish might move far enough to be exposed to harvest in Puget Sound, Washington. From 2008 to 2012, White Sturgeon of various sizes were acoustically tagged in the Pitt River ( n = 58) and in the lower reaches of the Fraser River (near Douglas Island, n = 52) to determine the timing, rate, and spatial extent of movements. Movements were monitored using acoustic receivers at 17 locations in the lowermost 92 km of the main-stem Fraser River, three in the first 21 km of the Pitt River (a tributary to the lower Fraser River), and nine in the coastal waters of British Columbia and Washington State. Travel speeds showed a strong skew toward slower movements (74% were <1 km/h) and did not differ significantly between upstream and downstream directions. On average, 33.2% of the sample was mobile (displacing ~13.4 km/month) and 66.8% was sedentary (displacing ~1.87 km/month). In general, White Sturgeon were significantly more sedentary during winter months and more mobile during spring and fall. Annual or seasonal migratory movements and patterns were observed for 73% of fish tracked. Repeated use of specific locations within the lower Pitt River during midwinter suggested White Sturgeon have a high fidelity for specific overwintering sites. Several of the tagged fish showed annual movements to the lowest reaches of the Fraser River for 1–3 months between May and September, although there was no direct evidence that they left the Fraser River and entered the Strait of Georgia. By contrast, there was strong evidence for extended and repeated movement into the lower Pitt River. Given that the lower Pitt River is outside the mark–recapture assessment area, our results suggest either that the area's boundaries need expansion, or alternative models should be considered for abundance estimations of lower Fraser River White Sturgeon. Received September 7, 2016; accepted February 3, 2017 Published online April 27, 2017